Объяснение:
у=2-3х; у+3х = 2 (все члены умножить на -4); -4у - 12х = -8;
5х+4у= -6; 5х+4у = -6; 4у + 5х = -6;
-7х = -14 (все члены разделить на -7);
х = 2.
х = 2; х = 2;
у= 2 - 3 * 2; у = -4.
1) x - 9y = -4 x - 9·1/3 = -4 x - 3 = -4 x = -4 + 3 x = -1
y = 1/3 y = 1/3 y = 1/3 y = 1/3 y = 1/3
ответ: (-1; 1/3)
2) x = 3y - 3 x = 3y - 3 x = 3y - 3 x = 3y - 3
5x - 2y = 11 5(3y - 3) - 2y = 11 15y - 15 - 2y = 11 13y = 26
x = 3y - 3 x = 3
y = 2 y = 2
ответ: (3; 2)
4х + 6y = 9|·3 12x + 18y = 27 12x + 18y = 27 20y + 8 + 18y = 27
3x - 5y = 2|·4 12x - 20y = 8 12x = 20y + 8 12x = 2y + 8
38y = 19 y = 0,5 y = 0,5 y = 0,5 y = 0,5
12x = 2y + 8 12x = 2·0,5 + 8 12x = 1 + 8 x = 9/12 x = 3/4 = 0,75
ответ: (0,75; 0,5).
Объяснение:
(2x-3y)^2=4x^2-12xy+9y^2